CLINICAL AND LABORATORY STUDIES ON CERTAIN ASPECTS OF HYPOMAGNESAEMIC TETANY IN CALVES: I. CLINICAL SIGNS AND ESTIMATION OF SOME BLOOD ELEMENTS AND ENZYMES - Nadeem, M.A.; Mahmoud, G.S.; Razak, W.A. (The Iraqi Journal of Veterinary Medicine, 1988)
This study was designed to determine for the first time in Iraq the clinical and biochemical changes occured in calves affected with hypomagnesaemic tetany. Fifty clinically normal calves and 50 calves showing symptoms of hypomagnesaemic tetany were used in the present study. Their ages ranged from 2-7 months. Clinical signs of affected animals were registered. Blood samples were taken from the 2 groups of animals to determine the levels of magnesium, calcium, phosphorous, potassium, sodium as well as 2 of the serum enzymes (SCOT & CPK). Tetany group of animals showed significantly decrease (P<0.01) in both Mg. & Ca levels reaching (0.804 ± 0.027) and (5.574 t 0.197) Mg./100 ml. serum respectively. The potassium levels were markedly increased (6.010 土 0.162) mEq/L. serum, while the phosphorous levels were dropped slightly. On the other hand, both serum enzymes (SGOT & CPK) were highly elevated (P < 0.01) and the data were (160.24 ± 4.881) unit/1 ml. serum and (781.516 ± 63.444) unit/1 liter serum respectively.